CORRELATION BETWEEN DEMOGRAPHIC PROFILE TOWARDS KNOWLEDGE AND ATTITUDE TO PREVENT DENGUE HEMORRHAGIC FEVER IN KARANGTENGAH CIANJUR - Adriana Damayanti; Gde Sindu Mega (Jurnal Kesehatan Masyarakat, 2022)
Dengue Hemorrhagic Fever (DHF) is a zoonosis caused by Aedes aegypti carrying Dengue Virus. West Java has the most DHF cases (20,85 cases per 100.000 people). Controlling the vector is the key to lower the incidence rate. Therefore, the quality itself depend on knowledge, attitude, and habit of household contributor. Housewives as the biggest household contributor play an important role to lower DHF rate. This study aimed to investigate the correlation between some women’s predictors such as education, income, occupation, and knowledge and attitude to prevent DHF. This was a cross sectional study involving 60 housewives taken by cluster random sampling which were 17-65-year-old and lived in BTN Sabandar, Cianjur Regency as the biggest DHF cluster in Karangtengah Public Health Center scope area. A day door-to-door questionnaire was used to investigate the correlation between demographic profile towards knowledge and attitude to prevent DHF. All the subjects met the study criteria. Of 26 respondent (43.3%) had satisfactory knowledge (mean: 74.56%) and 26 respondent (43.3%) had positive attitude (mean: 82.83%) to prevent DHF. Based on Gamma correlation, there was a weak and insignificant correlation between occupation (r: -0.067, p: 0.610), income (r: 0.164, p: 0.210), dan education (r: 0.017, p: 0.899) towards knowledge, and also between occupation (r: 0.045, p: 0.734), income (r: 0.005, p: 0.968), and education (r: 0.185, p: 0.157) towards attitude. There is a weak and insignificant correlation between occupation, income, and education towards knowledge and attitude to prevent DHF.